Evidence-based medicine III: level of evidence. Issue 4 (August 2019) - Kaefer, M.; Castagnetti, M.; Herbst, K.; Bagli, D.; Beckers, G.M.A.; Harper, L.; Kalfa, N.; Fossum, M.; ,
Summary: The present article is the third installment in a five-part series related to evidence-based medicine (EBM) provided by the European Society for Paediatric Urology Research Committee. It will present the different levels of evidence (i.e. systematic review, randomized controlled trial, cohort study) available to clinicians and researchers and describe the strengths of each study type. While EBM provides a valuable construct to aid in medical decision-making, it remains imperative that this information be interpreted and applied in the clinical context with a good dose of common sense.